2021
DOI: 10.1108/tqm-12-2020-0311
|View full text |Cite
|
Sign up to set email alerts
|

Customer lifetime value: investigating the factors affecting attitudinal and behavioural brand loyalty

Abstract: PurposeThis paper investigates the factors affecting customer lifetime value from an attitudinal and behavioural brand loyalty perspective in the Internet service industry. Specifically, willingness to pay more and word of mouth are categorised under attitudinal loyalty, while repurchase intention is classified under behavioural loyalty.Design/methodology/approachA self-administered questionnaire online survey via Google Forms was employed comprising a sample of 481 participants from the Internet service provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
(95 reference statements)
4
19
0
Order By: Relevance
“…The results of the SmartPLS analysis indicate a positive and significant influence between company image and customer satisfaction, which means that the better a company's image, the higher the satisfaction among customers. This is consistent with the research which shows that image has a positive effect on customer satisfaction (Dandis et al, 2021;Fauzi et al, 2022;Han & Hyun, 2017). Other studies have also shown that brand image significantly affects customer satisfaction (Mohammed & Rashid, 2018;Sharma et al, 2018;Yusfiarto et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the SmartPLS analysis indicate a positive and significant influence between company image and customer satisfaction, which means that the better a company's image, the higher the satisfaction among customers. This is consistent with the research which shows that image has a positive effect on customer satisfaction (Dandis et al, 2021;Fauzi et al, 2022;Han & Hyun, 2017). Other studies have also shown that brand image significantly affects customer satisfaction (Mohammed & Rashid, 2018;Sharma et al, 2018;Yusfiarto et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Channa et al (2022) found special treatment benefits significantly influence customer loyalty. Dandis and Eid (2022) contribute that special treatment benefits significantly impact WPM, WOM and RI. Similarly, Kim and Ok (2009) found special treatment benefits directly and indirectly impact affective commitment in the hospitality industry.…”
Section: Relational Benefits and Customer True Brand Loyaltymentioning
confidence: 96%
“…This position is supported by Yang et al (2017), who confirm that customer-CBs and identityrelated benefits precede other loyalty rewards and underpin incentives associated with loyalty programmes. Dandis and Eid (2022) found that confidence benefits significantly impact WPM, WOM and RIs. This position is supported by Gremler et al (2020), who found that loyalty is affected by relational benefits, although social and confidence benefits are more effective.…”
Section: Relational Benefits and Customer True Brand Loyaltymentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, loyalty is when customers repurchase/repeat behaviour, termed behavioural loyalty, and good word of mouth or favourable impression as attitudinal loyalty (Eid, 2021). However, studies rarely have taken these two dimensions (behavioural and attitude) together to determine whether customer repurchase response is profitable for marketers or the favourable impression they have for a brand (Kotler et al, 2019), retaining loyal consumers for online shopping platforms.…”
Section: Introductionmentioning
confidence: 99%